2009
DOI: 10.1016/j.lungcan.2008.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Expression of breast cancer resistance protein is associated with a poor clinical outcome in patients with small-cell lung cancer

Abstract: BCRP expression was significantly predictive of both response and progression-free survival (PFS) in SCLC patients receiving chemotherapy. These findings suggest that BCRP may play a crucial role in drug resistance mechanisms, and that it may serve as an ideal molecular target for the treatment of SCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
73
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 35 publications
1
73
0
Order By: Relevance
“…Expression of ABCG2 has been observed in the epithelial cells of the intestine, colon, liver canaliculi, renal tubules and placenta, where it eliminates anticancer drugs and ingested toxins (9). The association between overexpression of ABCG2, response to chemotherapy and prognosis has been ABCG2 expression in colorectal adenocarcinomas may predict resistance to irinotecan reported for leukemia (10) and various solid tumors, including breast cancer (11), oral squamous cell carcinoma (12), esophageal cancer (13) and lung cancer (14). Irinotecan and its active metabolite, SN-38, are included among the transport substrates of ABCG2 (15).…”
Section: Introductionmentioning
confidence: 99%
“…Expression of ABCG2 has been observed in the epithelial cells of the intestine, colon, liver canaliculi, renal tubules and placenta, where it eliminates anticancer drugs and ingested toxins (9). The association between overexpression of ABCG2, response to chemotherapy and prognosis has been ABCG2 expression in colorectal adenocarcinomas may predict resistance to irinotecan reported for leukemia (10) and various solid tumors, including breast cancer (11), oral squamous cell carcinoma (12), esophageal cancer (13) and lung cancer (14). Irinotecan and its active metabolite, SN-38, are included among the transport substrates of ABCG2 (15).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have identified genes or proteins in lung cancer whose expression levels are associated with response to antitumor drugs. The breast cancer resistant protein (BCRP), is one of the ABC transporters reported to be associated with resistance to anticancer drugs like doxorubicin, irinotecan, mitoxantrone, and its expression was found to be associated with a poor clinical outcome in SCLC patients undergoing chemotherapy [Kim, 2009]. Chiappori et al reported that RRM1 and Topo2 alpha proteins expression are biomarkers of chemotherapeutic efficacy in SCLC [Chiappori, 2010] and, recently, Usuda et al demonstrated that the expression levels of Klotho protein was correlated with the prognosis following resection in SCLC patients [Usuda, 2011].…”
Section: Targeting the Complex Biology Of Sclcmentioning
confidence: 99%
“…Several studies have identified genes or proteins in lung cancer whose expression levels are associated with response to antitumor drugs. The breast cancer resistant protein (BCRP), is one of the ABC transporters reported to be associated with resistance to anticancer drugs like doxorubicin, irinotecan, mitoxantrone, and its expression was found to be associated with a poor clinical outcome in SCLC patients undergoing chemotherapy [Kim, 2009]. Chiappori et al reported that RRM1 and Topo2 alpha proteins expression are biomarkers of chemotherapeutic efficacy in SCLC [Chiappori, 2010] and, recently, Usuda et al demonstrated that the expression levels of Klotho protein was correlated with the prognosis following resection in SCLC patients [Usuda, 2011].…”
Section: Targeting the Complex Biology Of Sclcmentioning
confidence: 99%